2022
DOI: 10.3390/v14081747
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of the RIPK3 Polyclonal Antibody and Its Application in Immunoassays of Nephropathogenic Infectious Bronchitis Virus-Infected Chickens

Abstract: Receptor interacting protein kinase 3 (RIPK3) is a vital serine/threonine kinase in regulating the programmed destruction of infected cells to defend against RNA viruses. Although the role of RIPK3 in viruses in mice is well characterized, it remains unclear where in nephropathogenic infectious bronchitis virus (NIBV) in chickens. Here, we use a self-prepared polyclonal antibody to clarify the abundance of RIPK3 in tissues and define the contributions of RIPK3 in tissue damage caused by NIBV infection in chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Many recent studies have reported that RIPK3 can independently promote cytokine release and the formation of inflammasome containing NLRP3 (186)(187)(188). Upon stimulation by danger-associated molecular patterns, the Pyrin structural domain of NLRP3 binds to apoptosis-associated speck-like proteins that contain cysteine-rich domain recruitment structural domains.…”
Section: Role Of Ripk1 and Ripk3 In Diabetic Nephropathymentioning
confidence: 99%
“…Many recent studies have reported that RIPK3 can independently promote cytokine release and the formation of inflammasome containing NLRP3 (186)(187)(188). Upon stimulation by danger-associated molecular patterns, the Pyrin structural domain of NLRP3 binds to apoptosis-associated speck-like proteins that contain cysteine-rich domain recruitment structural domains.…”
Section: Role Of Ripk1 and Ripk3 In Diabetic Nephropathymentioning
confidence: 99%